U/Pb and Nd data from Peñas Blancas Pluton, Northpatagonian Massif, Argentina - García, Valeria Adriana (2014)
First SHRIMP U-Pb isotopic analyses from Peñas Blancas pluton were carried out at Centro de Pesquisas Geocronológicas of São Paulo University. Five single zircon spots yield an Ordovician crystallization age of 471.0 ± 2.8 Ma.